PEMBERDAYAAN REMAJA UNTUK PERSIAPAN KEHAMILAN SEHAT PRANIKAH DI DESA SUKA MAJU KEC. MESTONG KAB. MUARO JAMBI TAHUN 2024 - Wuryandari, Ajeng Galuh; Simanjuntak, Ry Eny Mian Marisi (Universitas Baiturrahim, 2024)
Promoting premarital reproductive health is one way to help teens and prospective brides become better informed and capable of preparing for a safe pregnancy, which will help lower the number of stunts. The significance of pre-conception nutrition and the necessity for nutrition education and health promotion to enhance understanding and promote good habits in preparation for pregnancy. The objective of this project is to strengthen the involvement of young individuals in the community of Suka Maju Kec. Mestong Kab. Muaro Jambi in 2024, specifically in terms of preparation for a safe pregnancy and marriage. The activity commenced with a comprehensive assessment of the site and an analysis of the requirements of the partner regions, specifically two rural communities and a local facility. This was followed by a training session for 20 young females, which encompassed the significance of measuring nutritional status through anthropometric means, the proper classification of nutrient levels, the accurate utilisation of anthropometric tools, enhanced health promotion strategies for adolescents regarding balanced nutrition, preventative measures against nutritional issues in adolescents, and the role of adolescent leaders in mitigating stunting.